Pemetaan Riset Global Senyawa Fenolik dan Flavonoid dalam Sediaan Dekok (2015-2025): Analisis Bibliometrik dari Etnobotani dan Potensi Antioksidan - Dwi Endah Kusumawati; Davia Maulidda Suharno (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Decoction is a traditional extraction method rooted in ethnobotany; however, meeting quality standards in modern pharmaceutical research remains a major challenge. This study aims to map global research trends regarding phenolic and flavonoid compounds in decoctions over the 2015–2025 period through bibliometric analysis. Data were retrieved from the Scopus database and analyzed using VOSviewer 1.6.20 software, employing the fractional counting method to ensure a more proportional weighting of keyword relationships. The results indicate a fluctuating trend that significantly increased toward the end of the period, peaking at 78 documents in 2025, with India and China emerging as the primary contributors. Network visualization and research density analysis reveal that the global research focus remains centered on antioxidant capacity (DPPH, TPC, and TFC), while decoction itself occupies a supporting position within the research map. This study concludes that decoction has not yet become a central focus in modern pharmaceutical research but serves primarily as a vehicle for presenting active compounds. There remains a significant gap between traditional decoction use and the application of advanced analytical technologies such as HPLC and antibacterial testing, representing a substantial opportunity for future research to validate the safety and efficacy of decoctions more scientifically and through standardized approaches.